The correlation of HbA1c levels on the healing process of postoperative fractures in diabetes mellitus patients - Elanda Putri Madyaningtias; Arman Bausat; Jufri Latief; Nasser Mustari; Joko Hendarto; Prihantono Prihantono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Fracture is defined by the loss of bone or cartilage continuity, either total or partial. Diabetes mellitus (DM) is a group of metabolic diseases characterized by hyperglycaemia resulting from defects in insulin secretion, insulin action, or both. HbA1c could be used as a diagnostic tool and determines the glycaemic control of DM patients. This study aimed to investigate the correlation between serum HbA1c levels and the healing process of postoperative fractures in DM patients. This was an observational study with a retrospective cohort design. The study population was DM patients who were admitted to the Department of Emergency, Dr. Wahidin Sudirohusodo General Hospital, Makassar due to long bone fracture within the period of September 2019-February 2020. The bone fractures healing was evaluated based on the radiographic union scale in tibial fractures (RUST) scores. The results are analysed using the Chi-square test. A total of 70DM patients who underwent fracture reduction surgery were involved in this study. Out of 35 patients with controlled DM (HbA1c <7%), we obtained 24 (68.6%) patients and 11 (31.4%) patients with good and delayed union, respectively. The other 35 patients had uncontrolled DM (HbA1c >7%), and there were 13 (37.1%) patients and 22 (62.9%) patients with good and delayed union, respectively. The Chi-square test showed a significant relationship (p= 0.008). It can be concluded that the increase in HbA1c levels was related to the obstacles in bone fractures healing. Moreover, an infection contributes to the healing status of bone fractures.